Enhancing Higher Order Thinking Skills (HOTS) in Education: Strategies and Outcomes - Ragab, Aya; Kaid, Ahmed; Sayed, Ahmed Khamis (The Future of Education Journal, 2024)
This study investigated the effectiveness of higher-order thinking skills (HOTS)-focused teaching strategies on the development of critical thinking skills among first-year students in the Department of Education Technology at Sebelas Maret University, Surakarta, Indonesia. Despite increasing recognition of HOTS in education, there is a gap in empirical research examining its impact in Indonesian higher education contexts. Employing a quasi-experimental design, the research involved an intervention group utilizing HOTS-focused project-based learning and a control group receiving traditional instruction. Quantitative data from pre- and post-tests demonstrated statistically significant improvements in the intervention group’s critical thinking scores, with an average increase of 12.5 points compared to only 4.8 points in the control group. The effect size of 1.65 indicated a large and meaningful impact of the intervention. Qualitative feedback indicated higher engagement and enjoyment levels among students in the HOTS group. However, challenges such as time constraints and resource limitations were identified, highlighting barriers to effective implementation. The findings may not be fully generalizable to other settings due to the limited sample size and specific context of the study. Further research is needed to examine the effectiveness of other HOTS-focused teaching strategies and to address the challenges related to time constraints and resource limitations. These findings underscore the need for educational institutions to prioritize HOTS development through curriculum design and teacher training, paving the way for future research on long-term impacts and strategies for supporting educators.